A study of work from home infrastructure: a case study of intellectual property / Abdul Hafiz Muhammad - Muhammad, Abdul Hafiz (2015)
The needs of Work from Home implementation studies at Patent Examination Section are so demanding. This is because of the external problem and the internal problem. The external problem is the problem of the section to retain their experienced Patent Examiner with high rate turnover. The internal problem is the problems that always become a question in a Work from Home program. Through distance working environment, the problem with a supervision standard of procedure, the integrity of the staff and the security of the data always become a question. The aim of this research is to construct a Work from Home structure at MyIPO by proposing a Working from Home framework, a supervision application and construct a standard application running in Working from Home framework. This research is done by proposing a standard framework for MyIPO to implement a Work from Home program. As a result of this research, the Supervision Application is able to get the information of process running at Patent Examiner computer using WMI agent. Hopefully, this research will bring benefits and useful to MyIPO to implement a Work from Home Program.